Modulation of beta oscillations in the subthalamic area during motor imagery in Parkinson's disease. - Kühn, A; Doyle, L; Pogosyan, A; Yarrow, K; Kupsch, A; Schneider, G; Hariz, M; Trottenberg, T; Brown, P (2006)
Activation of the basal ganglia has been shown during the preparation and execution of movement. However, the extent to which the activation during movement is related to efferent processes or feedback-related motor control remains unclear. We used motor imagery (MI), which eliminates peripheral feedback, to further investigate the role of the subthalamic area in the feedforward organization of movement. We recorded local field potential (LPF) activity from the region of the subthalamic nucleus (STN) in eight patients with Parkinson's disease off dopaminergic medication during performance of a warned reaction time task. Patients were instructed to either extend the wrist [motor execution (ME)], to imagine performing the same task without any overt movement (MI), or, in a subgroup, to perform a non-motor visual imagery (VI) task. MI led to event-related desynchronization (ERD) of oscillatory beta activity in the region of the STN in all patients that was similar in frequency, time course and degree to the ERD occurring during ME. The degree of ERD during MI correlated with the ERD in trials of ME and, like ME, was accompanied by a decrease in cortico-STN coherence, so that STN LFP activity during MI was similar to that in ME. The ERD in ME and MI were both significantly larger than the ERD in VI. In contrast, event-related synchronization (ERS) was significantly smaller in trials of MI, and even smaller in trials of VI, than during ME. The data suggest that the activity in the region of the human STN indexed by the ERD during movement is related to the feedforward organization of movement and is relatively independent of peripheral feedback. In contrast, sensorimotor feedback is an important factor in the ERS occurring in the STN area after completion of movement, consistent with a role for this region in trial-to-trial motor learning or the re-establishment of postural set following movements.